Irritable Bowel Syndrome: New Approaches to Its Pharmacological Management - Gervais Tougas (Canadian Journal of Gastroenterology)
The present paper examines approaches to drug therapy for irritable bowel syndrome (IBS). Because IBS is associated with multiple symptoms, no single therapy is effective in all patients. However, issues such as affective and emotional factors also need to be addressed when treating patients with IBS. This paper emphasizes the importance of identifying new pharmaceutical approaches to treat a multitude of symptoms and obtaining a better understanding of the underlying mechanisms of IBS.